Nano ceramic composite rubber powder modified asphalt and preparation method thereof
By adding nanoceramic powder to TB powder modified asphalt and adopting specific preparation methods, the problem of insufficient deformation resistance at high temperature is solved, which significantly improves the high temperature and fatigue resistance and improves the road surface stability.
Patent Information
- Application Number
- CN202411588606.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-07
AI Technical Summary
TB powder modified asphalt has insufficient resistance to deformation at high temperatures, which limits its application and development.
Add nanoceramic powder to the TB glue powder modified asphalt, and use specific preparation methods, including heating and high-speed shear dispersion, to form nanoceramic composite glue powder modified asphalt, to improve its high-temperature deformation resistance and fatigue resistance.
It significantly improves the high-temperature deformation resistance and fatigue resistance of nanoceramic composite glue powder modified asphalt, reduces road surface diseases such as ruts and slitting, and retains the good low-temperature performance of TB glue powder.
Smart Images

Figure BDA0005124941190000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of road engineering, and in particular to a nano-ceramic composite rubber powder modified asphalt and a preparation method thereof. Background Art
[0002] Applying waste rubber powder to road paving materials is one of the main ways to achieve harmless treatment of waste tires. Rubber powder can significantly improve the adhesion, anti-aging and low-temperature crack resistance of asphalt, but rubber powder modified asphalt has problems such as excessive viscosity and insufficient storage stability.
[0003] In order to reduce the viscosity of rubber powder modified asphalt and improve its storage stability, high temperature is used to make the rubber powder undergo a thorough desulfurization and degradation reaction in the asphalt, and then SBS and sulfur are added to make a stable modified asphalt, namely TB (Terminal Blend) rubber powder modified asphalt. However, TB rubber powder modified asphalt has the problem of insufficient high temperature deformation resistance, which hinders its application and development.
[0004] Nanoceramics is a composite material that introduces nano-scale ceramic particles, whiskers, fibers, etc. into a ceramic matrix. The nano-scale grains and grain boundaries give it a special surface electronic structure and crystal structure, overcoming the brittleness of the ceramic itself, greatly improving the strength, toughness and ductility of the material, and having extremely high hardness and strength at high temperatures. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the problems existing in the above-mentioned existing nano-ceramic composite rubber powder modified asphalt and its preparation method, the present invention is proposed.
[0007] Therefore, the object of the present invention is to provide a nano-ceramic composite rubber powder modified asphalt and a preparation method thereof, which solves the problem of insufficient high-temperature deformation resistance of TB rubber powder modified asphalt.
[0008] To solve the above technical problems, the present invention provides the following technical solutions: a nano-ceramic composite rubber powder modified asphalt, the raw materials are calculated by weight and include: 100 parts of base asphalt, 12-20 parts of TB rubber powder, 2-4 parts of rubber oil, 2-5 parts of nano-ceramic powder, 1-2 parts of surfactant, and 0.2-0.4 parts of stabilizer.
[0009] As a preferred embodiment of the nano-ceramic composite rubber powder modified asphalt and its preparation method of the present invention, the desulfurized rubber powder is a road waste tire vulcanized rubber powder obtained by low-temperature crushing method, with a mesh size of 100-200, an ash content of not more than 8%, an acetone extract content of not more than 20%, a carbon black content of not less than 25%, a rubber hydrocarbon content of not less than 44%, a water content of <1%, and a Mooney viscosity of 30-50M.
[0010] As a preferred solution of the nano-ceramic composite rubber powder modified asphalt of the present invention, the average grain size of the nano-ceramic powder is 20-100 microns.
[0011] As a preferred embodiment of the nano-ceramic composite rubber powder modified asphalt of the present invention, the base asphalt is grade A 70# road petroleum asphalt with a softening point of ≥50°C.
[0012] As a preferred embodiment of the nano-ceramic composite rubber powder modified asphalt of the present invention, the stabilizer is sulfur; the surfactant is a high molecular weight alkyl ammonium salt copolymer; and the rubber oil is an aromatic oil prepared by a furfural extraction process.
[0013] A method for preparing nano-ceramic composite rubber powder modified asphalt comprises the following steps:
[0014] Step 1: Prepare raw materials, conduct technical performance tests on various raw materials, and weigh the raw materials according to the specified weight for use after they pass the tests;
[0015] Step 2: Prepare TB rubber powder composite modified asphalt, heat the base asphalt to 175-185°C and place it in a high-speed shear disperser, add rubber oil, and stir at a speed of 1000-2000 rpm for 15 minutes; then add TB rubber powder and perform high-speed shear dispersion on the mixture at a speed of 6000-7000 rpm for 40-50 minutes;
[0016] Step 3: Prepare nano-ceramic composite rubber powder modified asphalt, add nano-ceramic powder and surfactant, stir at a speed of 1000-2000 rpm for 15 minutes, then add stabilizer, develop at 180°C for 1-2 hours, and obtain nano-ceramic composite rubber powder modified asphalt.
[0017] Beneficial effects of the present invention: The present invention adds nano-ceramic material to TB rubber powder modified asphalt, utilizing the characteristics of high hardness, high fracture toughness and high wear resistance of the material at high temperature to improve the high-temperature deformation resistance and fatigue resistance of TB rubber powder modified asphalt, and reduce road surface diseases such as rutting and sliding. DETAILED DESCRIPTION
[0018] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0019] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0020] Example 1
[0021] 100 parts of base asphalt, 12 parts of TB rubber powder, 2 parts of rubber oil, 2 parts of nano ceramic powder, 1 part of surfactant, 0.2 parts of stabilizer
[0022] Nano-ceramic composite rubber powder modified asphalt was prepared as follows:
[0023] (1) Prepare raw materials: Conduct technical performance tests on various raw materials. After passing the tests, weigh the raw materials according to the specified weight for use;
[0024] (2) Preparation of TB rubber powder composite modified asphalt: First, the base asphalt was heated to 185°C and placed in a high-speed shear disperser, rubber oil was added, and stirred at a speed of 1000 rpm for 15 min; then TB rubber powder was added, and the mixture was subjected to high-speed shear dispersion at a speed of 6000 rpm for 50 min;
[0025] (3) Preparation of nano-ceramic composite rubber powder modified asphalt: Add nano-ceramic powder and surfactant, stir at a speed of 1000 rpm for 15 minutes, then add stabilizer, develop at 180°C for 2 hours, and obtain nano-ceramic composite rubber powder modified asphalt.
[0026] Example 2
[0027] 100 parts of base asphalt, 12 parts of TB rubber powder, 2 parts of rubber oil, 5 parts of nano ceramic powder, 2 parts of surfactant, 0.2 parts of stabilizer
[0028] Nano-ceramic composite rubber powder modified asphalt was prepared as follows:
[0029] (1) Prepare raw materials: Conduct technical performance tests on various raw materials. After passing the tests, weigh the raw materials according to the specified weight for use;
[0030] (2) Preparation of TB rubber powder composite modified asphalt: First, the base asphalt was heated to 185°C and placed in a high-speed shear disperser, rubber oil was added, and stirred at a speed of 1000 rpm for 15 min; then TB rubber powder was added, and the mixture was subjected to high-speed shear dispersion at a speed of 6000 rpm for 50 min;
[0031] (3) Preparation of nano-ceramic composite rubber powder modified asphalt: Add nano-ceramic powder and surfactant, stir at a speed of 1000 rpm for 15 minutes, then add stabilizer, develop at 180°C for 2 hours, and obtain nano-ceramic composite rubber powder modified asphalt.
[0032] Example 3
[0033] 100 parts of base asphalt, 20 parts of TB rubber powder, 3 parts of rubber oil, 2 parts of nano ceramic powder, 1 part of surfactant, 0.4 parts of stabilizer
[0034] Nano-ceramic composite rubber powder modified asphalt was prepared as follows:
[0035] (1) Prepare raw materials: Conduct technical performance tests on various raw materials. After passing the tests, weigh the raw materials according to the specified weight for use;
[0036] (2) Preparation of TB rubber powder composite modified asphalt: First, the base asphalt was heated to 185°C and placed in a high-speed shear disperser, rubber oil was added, and stirred at a speed of 1000 rpm for 15 min; then TB rubber powder was added, and the mixture was subjected to high-speed shear dispersion at a speed of 6000 rpm for 50 min;
[0037] (3) Preparation of nano-ceramic composite rubber powder modified asphalt: Add nano-ceramic powder and surfactant, stir at a speed of 1000 rpm for 15 minutes, then add stabilizer, develop at 180°C for 2 hours, and obtain nano-ceramic composite rubber powder modified asphalt.
[0038] Example 4
[0039] 100 parts of base asphalt, 20 parts of TB rubber powder, 3 parts of rubber oil, 5 parts of nano ceramic powder, 2 parts of surfactant, 0.4 parts of stabilizer
[0040] Nano-ceramic composite rubber powder modified asphalt was prepared as follows:
[0041] (1) Prepare raw materials: Conduct technical performance tests on various raw materials. After passing the tests, weigh the raw materials according to the specified weight for use;
[0042] (2) Preparation of TB rubber powder composite modified asphalt: First, the base asphalt was heated to 185°C and placed in a high-speed shear disperser, rubber oil was added, and stirred at a speed of 1000 rpm for 15 min; then TB rubber powder was added, and the mixture was subjected to high-speed shear dispersion at a speed of 6000 rpm for 50 min;
[0043] (3) Preparation of nano-ceramic composite rubber powder modified asphalt: Add nano-ceramic powder and surfactant, stir at a speed of 1000 rpm for 15 minutes, then add stabilizer, develop at 180°C for 2 hours, and obtain nano-ceramic composite rubber powder modified asphalt.
[0044] Comparative Example 1
[0045] 100 parts of base asphalt, 12 parts of TB rubber powder, 2 parts of rubber oil, 0.2 parts of stabilizer
[0046] TB rubber powder modified asphalt was prepared as follows:
[0047] (1) Prepare raw materials: Conduct technical performance tests on various raw materials. After passing the tests, weigh the raw materials according to the specified weight for use;
[0048] (2) Preparation of TB rubber powder composite modified asphalt: First, heat the base asphalt to 185°C and place it in a high-speed shear disperser, add rubber oil, and stir at a speed of 1000 rpm for 15 minutes; then add TB rubber powder and high-speed shear disperse the mixture at a speed of 6000 rpm for 50 minutes; add stabilizer and develop at 180°C for 2 hours to obtain TB rubber powder composite modified asphalt.
[0049] Comparative Example 2
[0050] 100 parts of base asphalt, 20 parts of TB rubber powder, 3 parts of rubber oil, 0.4 parts of stabilizer
[0051] TB rubber powder modified asphalt was prepared as follows:
[0052] (1) Prepare raw materials: Conduct technical performance tests on various raw materials. After passing the tests, weigh the raw materials according to the specified weight for use;
[0053] (2) Preparation of TB rubber powder composite modified asphalt: First, heat the base asphalt to 185°C and place it in a high-speed shear disperser, add rubber oil, and stir at a speed of 1000 rpm for 15 minutes; then add TB rubber powder and high-speed shear disperse the mixture at a speed of 6000 rpm for 50 minutes; add stabilizer and develop at 180°C for 2 hours to obtain TB rubber powder composite modified asphalt.
[0054] Performance Testing
[0055] The PG grade of asphalt was determined according to the performance-based asphalt binder grading specification of the US SHRP, and the performance test of the modified asphalt prepared in Examples 1-4 and Comparative Examples 1-2 was carried out according to the "Test Procedures for Asphalt and Mixtures for Highway Engineering" (JTGE20-2011). The asphalt mixture used SMA-13 grading and the asphalt-stone ratio was 5.5%. The experimental results are shown in Table 1:
[0056] Table 1 Comparison of performance test results of Examples 1-4 and Comparative Examples 1-2
[0057]
[0058] PG grading is an indicator for grading asphalt road performance, consisting of high temperature grade and low temperature grade, indicating that asphalt meets the use requirements within a certain temperature range. For example, PG76-22 means that the asphalt is suitable for areas where the maximum pavement design temperature does not exceed 76°C and the minimum pavement design temperature is not lower than -22°C.
[0059] The rutting factor is an indicator obtained through dynamic shear rheology test to evaluate the high temperature performance of asphalt. The larger the rutting factor, the stronger the surface asphalt's ability to resist flow deformation and the better the high temperature stability. The value is taken when the test temperature is 76°C.
[0060] The unconfined compressive strength of asphalt mixture is obtained through uniaxial compression test.
[0061] Dynamic stability refers to the number of times the asphalt mixture rutting specimen travels under the standard axle load for every 1 mm deformation under high temperature conditions. It is used to evaluate the high-temperature deformation resistance of the asphalt mixture.
[0062] Fatigue life refers to the number of stress cycles when the microstrain is 1250 εμ and the stiffness modulus of the asphalt mixture beam is reduced to 50% of the initial stiffness modulus in the four-point beam bending fatigue test with controlled strain. The more cycles, the stronger the fatigue resistance of the asphalt mixture.
[0063] Comparative Example 1-2 is common TB rubber powder modified asphalt.
[0064] From the above experimental data, we can know that:
[0065] Comparing Examples 1 and 3, and Examples 2 and 4, when the TB rubber powder content is constant, as the nano-ceramic powder content increases, the compressive strength, high temperature performance, and fatigue performance of the composite modified asphalt are significantly improved.
[0066] Comparing Examples 1 and 2, and Examples 3 and 4, under the condition of a certain nano-ceramic powder content, as the TB rubber powder content increases, the low-temperature performance of the composite modified asphalt is improved.
[0067] From the data of Examples 1-4 and Comparative Examples 1-2, it can be seen that the nano-ceramic composite rubber modified asphalt still retains the excellent low temperature performance of TB rubber powder. Compared with TB rubber powder modified asphalt, the compressive strength, high temperature performance and fatigue performance are significantly improved.
[0068] In summary, the nano-ceramic composite rubber modified asphalt prepared by the technology of the present invention can retain the good low-temperature performance of TB rubber powder while having higher strength, high-temperature performance and fatigue performance, and significantly improves road surface diseases such as rutting and sliding.
[0069] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A nano-ceramic composite rubber powder modified asphalt, characterized in that: The raw materials include, by weight: 100 parts of base asphalt, 12-20 parts of TB rubber powder, 2-4 parts of rubber oil, 2-5 parts of nano ceramic powder, 1-2 parts of surfactant, and 0.2-0.4 parts of stabilizer.
2. The nano-ceramic composite rubber powder modified asphalt according to claim 1, characterized in that: The desulfurized rubber powder is vulcanized rubber powder of waste road tires obtained by low-temperature pulverization, with a mesh size of 100-200, an ash content of no more than 8%, an acetone extract content of no more than 20%, a carbon black content of no less than 25%, a rubber hydrocarbon content of no less than 44%, a water content of <1%, and a Mooney viscosity of 30-50M.
3. The nano-ceramic composite rubber powder modified asphalt according to claim 2, characterized in that: The average grain size of the nano ceramic powder is 20-100 microns.
4. The nano-ceramic composite rubber powder modified asphalt according to claim 1, characterized in that: The matrix asphalt adopts A-grade 70# road petroleum asphalt with a softening point of ≥50°C.
5. The nano-ceramic composite rubber powder modified asphalt according to claim 4, characterized in that: The stabilizer is sulfur; the surfactant is a high molecular weight alkyl ammonium salt copolymer; and the rubber oil is an aromatic oil prepared by a furfural extraction process.
6. A method for preparing nano-ceramic composite rubber powder modified asphalt, characterized in that: The following steps are involved: Step 1: Prepare raw materials, conduct technical performance tests on various raw materials, and weigh the raw materials according to the specified weight for use after they pass the tests; Step 2: Prepare TB rubber powder composite modified asphalt, heat the base asphalt to 175-185°C and place it in a high-speed shear disperser, add rubber oil, and stir at a speed of 1000-2000 rpm for 15 minutes; then add TB rubber powder and perform high-speed shear dispersion on the mixture at a speed of 6000-7000 rpm for 40-50 minutes; Step 3: Prepare nano-ceramic composite rubber powder modified asphalt, add nano-ceramic powder and surfactant, stir at a speed of 1000-2000 rpm for 15 minutes, then add stabilizer, develop at 180°C for 1-2 hours, and obtain nano-ceramic composite rubber powder modified asphalt.